Brown Basilisks in Florida - Kenneth T. Gioeli; Steve A. Johnson; Amanda Thompson (EDIS, 2022)
This publication presents information about the nonnative lizard Basiliscus vittatus (brown basilisk) in Florida. It contains information about brown basilisk identification, natural history, and distribution in Florida. The intended audience includes homeowners and land managers primarily in central and south Florida.